Bentuk Penyajian Koreografi Tari Risak - Apriyani, Anisa (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Risak Dance is a dance choreography inspired by phenomena that occur in the school or community environment and tend to be experienced by women, namely Bullying. Bullying can attack anyone and anywhere, starting from public places or even in the public sphere. The impact of bullying can cause the victim’s psyche to become stressed, depressed, and even traumatized to make friends, so that the victim becomes a more introverted and lonelier person. The purpose of writing is to know and describe the Form of Presentation of Risak Dance Choreography. This writing uses a qualitative descriptive method. The data collection technique is in the form of a literature study. The results of the writing describe that in this case the basic elements of dance will be used as expressed by Sal Murgiyanto (1983:19), regarding the form of dance presentation consisting of dancers, dance movements, music, makeup, costumes, props, floor patterns and performance venues.